Wage Equality in a General Equilibrium Model with Indivisibilities - Kala Krishna; Cemile Yavas (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
This paper looks at some consequences of a comittment to wage equality in some sectors of the economy which produce lumpy consumer goods. We show that in this setting, there are two equilibria, with high or low wages, incomes and output. In this closed economy, growth may be immiserizing. We also show that redistribution may eliminate the low wage equilibrium in productive economies but in unproductive ones it eliminates the market for indivisible good itself! This suggests why redistribution could be a rich man's game.
Keywords: 330; Vergütungssystem; Allgemeines Gleichgewicht; Theorie